Sirolimus quantification by high-performance liquid chromatography with ultraviolet detection - Andrade, Maria Claudina Camargo de [UNIFESP] (2005)
The need to adapt optimal conditions of sirolimus blood level monitoring in laboratories led us to optimize an high-performance liquid chromatography-ultraviolet method and compare the elution performances using the mobile phase A, 68% MeOH/2% acetonitrile (ACN)/30% H2O and mobile phase B, 30% MeOH/42% ACN/28% H2O. Samples were assayed with 1-chlorobutane, redissolved in MeOH/water and injected onto a C-18 column at 50 degrees C. the assay achieved sensitivity of 2.5-150 ng/ml (CV = 10.6%) and recovery of 92-103.6%. the intra- and interassay precisions ranged from 3.3% to 13% and from 5.9% to 15% for quality controls of 7.5, 60 and 120 ng/ml. the mobile phase A was unable to elute and recover sirolimus and internal standard in the expected retention time and concentration. Under our working conditions, the assay was precise, accurate and sensible, stressing the importance of establishing for the best working conditions according to the staff and demands of the laboratory.